Frost resistance in the tropical palm Euterpe edulis and its pattern of distribution in the Atlantic Forest of Argentina - Gatti, Maria Genoveva (2008)
Frost resistance and subzero temperature effects on photosynthesis, survival and distribution were studied in Euterpe edulis, a tree palm species of the Atlantic Forest, near the southern limit of the species distribution. E. edulis grows under the forest canopy and is absent from forest stands located near bottom valleys. This palm species has been commercially exploited for palm hearts, making it the most important non-timber forest species in North-Eastern Argentina. Its distribution was studied in relation to the frequency and intensity of subzero temperatures along a topographic gradient. E. edulis abundance was higher at the highest site and decreased or became absent towards the lowest site. Subzero temperatures during each of three winter seasons were observed in the lowest site. The medium and high elevation sites never experienced absolute minimum temperatures below 0 °C. Forest structure, fraction of solar radiation transmitted through the canopy and soil water potentials did not change substantially along the gradient. After a low temperature period in winter, the maximum quantum yield in E. edulis leaflets was relatively low in individuals at the low elevation site while having normal values at the medium and high elevation sites. Thermal analysis indicated that E. edulis saplings can supercool down to about -10 °C and do not tolerate extracellular ice formation. Ice formation was observed at about -4 °C, relatively close to the equilibrium freezing temperature, only after an increase in ambient humidity resulted in dew formation on the plant surface. Dew formation is commonly observed in valleys during the winter season. This observation gives further support to the hypothesis that strong infrequent frost events could be an important environmental factor determining the spatial distribution pattern of E. edulis in the Atlantic Forest of Argentina.